A bibliometric analysis of cerebral palsy from 2003 to 2022 - Yue Hu; Yadan Zheng; Yue Yang; Wenfeng Fang; Maomao Huang; Dan Li; Zhangyu Xu; Fangyuan Xu; Jianxiong Wang; Jianxiong Wang; Jianxiong Wang (Frontiers in Neurology, 2024)
PurposeThis bibliometric study explores cerebral palsy (CP) research from 2003 to 2022 to reveal the topic hotspots and collaborations.MethodsWe retrieved studies on CP from the Web of Science Core Collection from 2003 to 2022 and then used CiteSpace and Bibliometrix to perform a bibliometric analysis and attain knowledge mapping, including publication outputs, funding, journals, authors, institutions, countries/territories, keywords, collaborative relationships, and topic hotspots.ResultsIn total, 8,223 articles were published from 2003 to 2022. During this period, the number of publications increased continuously. Developmental Medicine and Child Neurology was the most productive and frequently co-cited journal. Boyd was the most productive and influential author, with 143 publications and 4,011 citations. The United States and Vrije Universiteit Amsterdam were the most productive countries and institutions, respectively. Researchers and institutions from the USA, Australia, and Canada constituted the core research forces, with extensive collaborations worldwide. The most common keywords were gait (553), rehabilitation (440), spasticity (325), botulinum toxin (174), therapy (148), upper extremity (141), quality of life (140), disability (115), pain (98), electromyography (97), kinematics (90), balance (88), participation (85), and walking (79).ConclusionThis study provides a systematic and comprehensive analysis of the CP-related literature. It reveals that Developmental Medicine and Child Neurology is the most active journal in this field. The USA, Vrije Universiteit Amsterdam, and Boyd are the top countries, institutions, and authors, respectively. Emerging treatment methods, complication management, and functional recovery comprise the future research directions and potential topic hotspots for CP.